2002
DOI: 10.1046/j.1439-0442.2002.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Fibrin Glues in Anastomoses and Skin Closure

Abstract: To control intra-operative haemorrhage, fibrin glues are preferred by many surgeons because of their biological advantages and convenience of application. Manufacturers have developed a few kinds of fibrin glues with a little difference in their composition. This study was to compare the effectiveness of two commercially available fibrin glues; Greenplast (Green Cross P. D. Company, Yongin, Korea) and Tisseel (Baxter-Immuno AG, Vienna, Austria). They were applied experimentally to several kinds of surgery in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…In an experimental study of renal vessel anastomoses, Park et al [3] compared two different products (Greenplast; Green Cross P.D. Company, Yongin, Korea vs. Tisseel; Baxter-Immuno AG, Vienna, Austria) and found that the two-component fibrin glues had similar effects on hemostatic modulation, mechanical barrier and adhesive outcomes, and no complications ensued after the use of either.…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study of renal vessel anastomoses, Park et al [3] compared two different products (Greenplast; Green Cross P.D. Company, Yongin, Korea vs. Tisseel; Baxter-Immuno AG, Vienna, Austria) and found that the two-component fibrin glues had similar effects on hemostatic modulation, mechanical barrier and adhesive outcomes, and no complications ensued after the use of either.…”
Section: Introductionmentioning
confidence: 99%
“…The method of tissue adaptation is therefore limited by free moving space thus revealing conventional suturing unsuitable. Fibrin based adhesives or glues achieve insufficient tensile strength for suture replacement and are further limited by early resorption [10,11]. These products can be used as temporary sealants or hemostatic agents.…”
Section: Introductionmentioning
confidence: 99%
“…An additional seven studies have been performed using animal models. [5][6][7][8][9][10][11] To our knowledge, no studies have evaluated ostomy creation using tissue adhesives. The present study thus features several IRB-mandated restrictions to ensure patient safety during ostomy creation, including using two sutures and an ostomy rod before tissue adhesives could be used alone.…”
Section: Uchino Ikeuchi Bando Sasaki Chohno Horio Takesuementioning
confidence: 99%